THE ORIENTATION TOWARDS THE VIETNAMESE REVOLUTION OF THE WORK “ĐƯỜNG KÁCH MỆNH” OF HO CHI MINH - Gam, Dr. Huynh Thi (The journal of contemporary issues in business and government, 2021)
The work “Đường kách mệnh” (Revolutionary way) is one of the typical works, containing the great theoretical and practical value, playing an important role in spreading Marxism-Leninism into Vietnam, in combining worker movement and patriotism with Marxism, creating ideological and theoretical premises for the birth of the Communist Party of Vietnam. More than ninety years have passed, but the theoretical values of revolutionary morality, the goal of national independence and socialism, the leading role of the party organization are still valid become the standards for building a new morality, building the socialist rule of law State in Vietnam. Based on those practical values, this study continues to clarify the value of the work “Revolutionary way” in the current period of Vietnam.